Gender Differences in Abusive Parenting among Incarcerated Parents in Japan - Sasaki, Ayako (The prison journal, 2023)
This study examined the prevalence and risk factors of abusive parenting among the incarcerated population in Japan. Using a national survey of incarcerated parents (95 women and 79 men), the results showed that incarcerated mothers are at greater risk of abusive parenting and that childhood abuse history predicted abusive parenting for mothers but not for fathers. On the other hand, intimate partners’ parental attitudes impacted the abusive parenting of both incarcerated mothers and fathers, but differed by gender. Special attention was given to gender differences throughout the study, aiming to guide gender-responsive parenting programs in correctional settings.